Dinamika Ekonomi Konvensional: Kapitalisme Dan Sosialisme Dalam Perspektif (Gunung Djati Conference Series, 2025)
Capitalist and socialist economies are two major economic systems withfundamental differences in resource management and wealth distribution.Capitalism emphasizes private ownership and market mechanisms, while socialismfocuses on the role of the state in regulating the economy to achieve collectivewelfare.This study employs a qualitative descriptive approach by analyzingliterature and secondary data related to these two economic systems. The articleexplores the fundamental principles, advantages, and weaknesses of eachsystem.